2023
DOI: 10.1186/s13148-023-01573-y
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine formula Huazhuo Tiaozhi granule ameliorates dyslipidaemia via regulating histone lactylation and miR-155-5p biogenesis

Xiangjun Yin,
Min Li,
Yongzhi Wang
et al.

Abstract: Background Huazhuo Tiaozhi granule (HTG) is a herbal medicine formula widely used in clinical practice for hypolipidaemic effects. However, the molecular mechanisms underlying dyslipidaemia treatment have not been well elucidated. Results A significant reduction in the levels of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) was observed in the serum of patients with dyslipidaemia after HTG treatment, without disruption in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Yin et al demonstrated that lactylation was observed in 198 proteins after HTG treatment, including histone H2B (K6) and H4 (K80) lactylation. HTG promoted lactylation in hepatocytes, further validating lactylation modification as one of the important targets for regulating lipid metabolism [166].…”
Section: Obesity Diabetes and Lactylationmentioning
confidence: 88%
“…Yin et al demonstrated that lactylation was observed in 198 proteins after HTG treatment, including histone H2B (K6) and H4 (K80) lactylation. HTG promoted lactylation in hepatocytes, further validating lactylation modification as one of the important targets for regulating lipid metabolism [166].…”
Section: Obesity Diabetes and Lactylationmentioning
confidence: 88%
“…To acquire insight into the proteomic profile of HpEVs, the identified proteins were screened in several databases and analyzed using bioinformatics methods, as described in previous reports [57][58][59][60]. Briefly, hierarchical clustering analysis was carried out using the R Package pheatmap (v.2.0.3 https://cran.r-project.org/web/packages/cluster/, accessed on 3 March 2020), and the heat map was produced by a dendrogram depicting the extent of similarity in the protein expression among samples.…”
Section: Bioinformatics Analysismentioning
confidence: 99%